Ecological conditions and isotopic diet (13C and 15N) of Holocene caviomorph rodents in Northern Patagonia. (April 2016) - Fernández, Fernando J.; Gil, Adolfo; Ugan, Andrew; Neme, Gustavo
Abstract: This work improves our knowledge about the relationship between diet and environment among Northern Patagonian caviomorph rodents. In order to characterize long-term individual diets, we present δ 13 C and δ 15 N data from osteological remains of the caviomorph rodents Dolichotis patagonum, Myocastor coypus, Lagostomus maximus, Lagidium viscacia, Microcavia australis, Galea leucoblephara and Ctenomys sp., recovered from archaeological and recent contexts. These data are analyzed by temporal and geographic context and compared with the previous dietary studies based on macrorremains and microhistological analysis. Significative differences were found between rodents from Monte and Patagonian phytogeographic provinces, as well as between archaeological and modern members of the genus Ctenomys, indicating diet changes between Late Holocene and recent times individuals, that could confirm the climatic variations and/or the recent overgrazing effect. The results indicate trends in rodent diets of 20th and 21st centuries were different to those of the Late Holocene, suggesting a decrease in precipitation and/or an increase of the summer pattern of the same, and/or an increase of mean annual temperature. In addition, this work confirms the generalist strategy of several taxa, although mainly in Ctenomys, which its diet co-varies with these environments. Highlights: Isotopic diets of rodents from archaeological and recent contexts of North Patagonia were studied. Agreement between isotopic and histological values of many caviomorph rodents. Geographic differences in diets of rodents inhabiting Monte and Patagonian regions. Temporal changes in isotope values and inferred diet among the genus Ctenomys . The latter appear related to vegetation changes, recent warming, and overgrazing.